Book Review - Inquiry as Stance: Practitioner Research for the Next Generation - Jen Scott Curwood (Networks: An Online Journal for Teacher Research, 2011)
In Inquiry as Stance: Practitioner Research for the Next Generation, the sequel to Inside/Outside, the authors note that educators now find themselves teaching and learning in “trying times” (p. 5). Marked by test-based accountability, annual school progress reports, and pay-for-performance, the era of No Child Left Behind often threatens to undermine the agency and pedagogy of educators. But at the same time, Cochran-Smith and Lytle point out that “more and more practitioners are now expected to be the gatherers and interpreters of school and classroom data as part of larger initiatives to improve school achievement” (p. 1). Rather than leaving decisions in the hands of policymakers or administrators, Cochran-Smith and Lytle suggest that educators can play key roles in the design, implementation, and evaluation of educational reforms. As a result, practitioner research should be considered vital for the success of large-scale reforms as well as for the development of teacher knowledge and practice. In using the phrase “inquiry as stance,” the authors posit that educators’ learning, knowing, doing, and being are also part and parcel of broader movements for social change and social justice.